2020
DOI: 10.1177/1464420720951889
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior improvement of hardened parts using sequential hard turning, grinding, and ball burnishing operations

Abstract: One of the major problems encountered in hardened components such as roller bearings, which work under fatigue loading conditions, is that the requirement of higher surface finishes (≈0.15 µm Ra) cannot be achieved by the sequential hard turning and ball burnishing processes. Such high surface qualities can be generated by additional finishing operations such as grinding. However, despite the improvement in the surface roughness, the grinding process increases both the tensile surface residual stresses and cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Fonte et al (Fonte et al, 2007) showed results for the fatigue crack surface roughness Ra and Rz according to ISO 4287 (ISO, 1997) with the fatigue crack propagation direction at the center of fracture surface. Although similar roughness results were achieved at the center and at the both sides of the fracture, areal surface Sx parameters according to ISO 25178 (ISO, 2012;Arsalani et al, 2020;Yang et. al., 2019) give complete information because a single line cannot identify pits or valleys and show the relationship between surface function, as confirmed by Stach et al (Stach et al, 2017).…”
Section: Introductionsupporting
confidence: 65%
“…Fonte et al (Fonte et al, 2007) showed results for the fatigue crack surface roughness Ra and Rz according to ISO 4287 (ISO, 1997) with the fatigue crack propagation direction at the center of fracture surface. Although similar roughness results were achieved at the center and at the both sides of the fracture, areal surface Sx parameters according to ISO 25178 (ISO, 2012;Arsalani et al, 2020;Yang et. al., 2019) give complete information because a single line cannot identify pits or valleys and show the relationship between surface function, as confirmed by Stach et al (Stach et al, 2017).…”
Section: Introductionsupporting
confidence: 65%
“…The compressive residual stresses provide an additional protection against surface-initiated spalling [5]. Therefore, the compressive stresses are desired to form instead of tensile stresses on raceways of bearing rings since they improve the fatigue life [6,7]. L50 theoretical life value (average life) determined using MESYS Rolling Bearing Calculation program under above-mentioned test conditions and lubrication parameters was found to be 431 hours.…”
Section: Fatigue Lifementioning
confidence: 99%
“…It is well-known that hard turning processes in which cutting inserts with negative rake angle are employed produce the compressive stresses. Unlike compressive stresses, tensile stresses have a negative effect on fatigue life of machinery components as they lead to the crack initiation and rapid crack propagation [4][5][6][7][8]. They can occur in aggressive grinding conditions due to thermal shocks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the TRS of 1223 MPa formed during turning of AISI 4130 steel has been transformed into CRS of −223.7 MPa by deploying ball burnishing process. 15 Also, it has been observed that the ball burnished surface delayed the fatigue crack propagation in stress concentration zones, thereby improving the fatigue strength drastically. 16 In recent times, machine learning techniques have become quite popular in modelling complex engineering problems precisely and are being regarded as a substitution for classical modelling methods.…”
Section: Introductionmentioning
confidence: 99%